Changes in neutrophil count, creatine kinases and muscle soreness after repeated bouts of downhill running - Smith, LL; Semple, SJ; McKune, AJ; Neveling, N; Caldeira, M; Swanepoel, J-M; Tsomele, L; Naidoo, M; Sibanda, E (South African Journal of Sports Medicine, 2007)
Objective. A primary objective was to examine circulating neutrophil count after repeated bouts of downhill running. An additional aim was to determine creatine kinase (CK) levels during the initial 12 hours, after repeated DHRs. Design. Eleven healthy, untrained Caucasian males performed 2 x 60 min bouts of DHR (-13.5%), spaced 14 days apart, at a speed equal to 75% VO2max on a level grade. Blood was collected before, after, and every hour for 12 hours, and every 24 hours for 6 days. Absolute neutrophil count, CK, and delayed-onset muscle soreness (DOMS) were assessed. Results were analysed using repeated measures ANOVA (p